Populism Amidst Prosperity: Poland's Growth Model and its Socio-Political Outcomes - Nina Lopez Uroz (London School of Economics and Political Science (LSE), European Institute, 2020)
Poland is an example of both successful economic transition from communism and democratic backsliding. By applying the crucial case study method, this paper explores how the Polish version of the dependent market economy has led to relative deprivation and political instability. The distributional consequences of this growth model are analysed by looking at three indicators, namely wages, income inequality and temporary employment. While it seems at first that the electoral results of the radical-right populist Law and Justice party cannot be explained by socio-economic factors, this paper argues that distributional outcomes have acted as a deeper variable for the party's success. Growing discontent stemmed from gradually deteriorating economic perspectives for key social blocs. More broadly, in combination with a supply-side analysis of party system change, this paper seeks to identify the socioeconomic conditions under which a populist party can thrive and questions the political viability of the dependent market economy.
Keywords: 330; growth model; Poland; relative deprivation; labour market segmentation; populism